Model for Estimating Waste Generation in Pekanbaru Using Backpropagation Algorithm - Farahdina Risky Ramadani; Inggih Permana; M. Afdal; Siti Monalisa (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
Waste generation in Pekanbaru City cannot be managed optimally. Based on 2020 data, less than 50% of the waste that reaches the Final Disposal Site (TPA) reaches. To overcome this problem, this study aims to create an estimation model that can estimate the amount of waste generated each year. So that it can help the authorities to implement various policies to control waste generation. The estimation model is created using the backpropagation algorithm. The attributes used are those related to population and waste generation. Based on the results of experiments conducted using RapidMiner, the best network architecture model is the 6-6-1 model, namely six nodes in the input layer, six nodes in the hidden layer, and one node in the output layer. The six nodes in the input layer refer to the number of attributes used. The activation function used is binary sigmoid. The RMSE value generated from the best model is very low, namely 0.0181. So it can be concluded that this model can be used to estimate the generation of solid waste in Pekanbaru City